PENGARUH KONFLIK KERJA DAN STRES KERJA TERHADAP KINERJA PEKERJA GEN Z DI BANDAR LAMPUNG - Santoso, Shintia; Saputra, Febrian (STKIP Persada Khatulistiwa Sintang, 2024)
Human resources are the most important asset of a company, in order to achieve the desired goals a company requires good management, especially human resources. Good human resource management is believed to be able to provide optimal performance for the company. This research aims to examine the influence of work conflict and work stress on the performance of Gen Z workers in Bandar Lampung. This type of research is quantitative research. The research was conducted on all Bandar Lampung employees with a total of 160 respondents. The data collection technique is using a questionnaire distributed to Gen Z workers with employee status in Bandar Lampung. Data processing and analysis techniques use validity tests, reliability tests, partial tests (T), simultaneous tests (F), multiple linear regression analysis and coefficient of determination. The research results show that partially work conflict has no significant effect on employee performance and partially work stress has a significant effect on employee performance. Simultaneously, work conflict and work stress have a significant effect on employee performance.